2005
DOI: 10.1148/radiol.2353040121
|View full text |Cite
|
Sign up to set email alerts
|

Airway Wall Thickness in Cigarette Smokers: Quantitative Thin-Section CT Assessment

Abstract: This software provides accurate and reproducible measurements of IA and WA of bronchi on thin-section CT images and demonstrates that in vivo normalized airway wall thickness was larger in smokers with COPD than it was in smokers or nonsmokers without COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
113
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(116 citation statements)
references
References 28 publications
0
113
1
2
Order By: Relevance
“…In COPD, the quantitative evaluation of the airways using CT has received less attention than the analysis of emphysema. In fact, there have been only a few such studies (27)(28)(29)(30). Nakano and colleagues were the first to report that wall thickening at B1 in the right upper lobe had a significant correlation with FEV 1 (% predicted) (27), and they subsequently demonstrated that measuring airway dimensions in large airways could roughly estimate small airway dimensions by comparing the CT findings of large airways with the histologic measurement of small airways in lungs excised from the same subjects (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In COPD, the quantitative evaluation of the airways using CT has received less attention than the analysis of emphysema. In fact, there have been only a few such studies (27)(28)(29)(30). Nakano and colleagues were the first to report that wall thickening at B1 in the right upper lobe had a significant correlation with FEV 1 (% predicted) (27), and they subsequently demonstrated that measuring airway dimensions in large airways could roughly estimate small airway dimensions by comparing the CT findings of large airways with the histologic measurement of small airways in lungs excised from the same subjects (28).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it has been suggested that CT can be used to evaluate airway dimensions in a variety of diseases (21)(22)(23)(24)(25)(26). However, there have been only a few studies that have focused on measuring the airway dimensions in patients with COPD (27)(28)(29)(30). Nakano and colleagues were the first to report that wall thickening in the apical bronchus of the right upper lobe had a significant correlation with FEV 1 (% predicted) in patients with COPD (27).…”
mentioning
confidence: 99%
“…Rays that project into the neighboring blood vessel have been manually removed. Modified by permission from Reference 44. general was associated with thicker airway walls and showed that subjects with COPD had thicker airway walls than smokers or nonsmokers without COPD (41). A study by Aziz and coworkers used a combination of quantitative CT analysis, qualitative texture assessment, and qualitative airway analysis to assess the different morphologic features present in subjects with COPD (41).…”
Section: Phenotyping Of Copd Using Computed Tomographymentioning
confidence: 99%
“…Matsouka et al have studied with a healthy group. Berger et al have also demonstrated that in vivo normalized airway wall thickness was larger in smokers with COPD than it was in smokers or nonsmokers without COPD 22) . Therefore age and smoking should be taken into consideration in case of measurement of bronchus wall in larger series due to the controversies in previous studies.…”
Section: Discussionmentioning
confidence: 94%